Effects of block periodization of high-intensity interval training sessions on VO2 max in subelite and elite athletes - Vogt, M.; Brel, F.; Weber, S.; Wisskopf, R.; Schlegel, C.; Hoppeler, H. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
High-intensity aerobic interval training is very effective in improving VO2max in subjects of various fitness levels (2, 5). In highly-trained athletes, concurrent strength and endurance training programs may compromise the adaptive response to such high-intensity training sessions (1, 3). According to the alternative concept of block periodization (3, 4), we tested the effects of 7-14 days high-intensity interval training blocks in endurance trained subjects, elite cross country skiers, and junior and world class alpine skiers. Methods & Results: Study 1: 7 endurance-trained subjects (VO2max: 58.5 +/- 4.9ml/min/kg) performed 18 sessions of 4 x 4-min interval training on a cycle ergometer at 90-95% of HRmax in 14 days. Increase in VO2max (mean: +5.6 +/- 3.2%) was positively correlated to training intensity (r = 0.81, p < 0.05) Study 2: During the summer preparation period, 9 elite cross country skiers (68.3 +/- 4.8ml/min/kg) performed three 5-day high-intensity interval training blocks separated by 4-week base training periods. Athletes were advised to execute all sessions at intensities above individual ventilatory threshold 2. VO2max increased by 6.4 +/- 4.2% (p < 0.001) Study 3: 9 male (54.2 +/- 3.1ml/min/kg) and 4 female (50.4 +/- 6.6ml/min/kg) junior alpine skiers performed 12 cycle ergometer and 3 obstacle-run 4 x 4-min interval training sessions at 90-95% of HRmax in 11 days. VO2max and ski-specific field test scores increased in male skiers (+7.4 +/- 2.9%, p < 0.001; +8.8 +/- 3.9%, p = 0.001) but not in female skiers (+2.2 +/- 1.3%, p = 0.35; -7.6 +/- 3.1%, p = 0.06). Study 4: Three world class alpine skiers performed 8 - 10 interval training sessions at 90-95% of HRmax in 14 days, followed by a 14-day low-intensity (<75% HRmax) high-volume (700 km) training period. All athletes improved VO2max (mean: +11.1%) and maximal power output (+7.3%). Conclusion: With a mean duration of only 13 days, high-intensity interval block training is very efficient in improving VO2max (on average by 6.5% or 0.5% per session) and performance. It should be considered that this adaptive response might be influenced by differences in training intensity (study 1) as well as gender (study 3). Persistent fatigue after the intensity block may be an issue.